2017
DOI: 10.1194/jlr.m079897
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of TG accumulation and lipid droplet morphology by the novel TLDP1 in Aurantiochytrium limacinum F26-b

Abstract: Thraustochytrids are marine single-cell protists that produce large amounts of PUFAs, such as DHA. They accumulate PUFAs in lipid droplets (LDs), mainly as constituent(s) of triacylglycerol (TG). We identified a novel protein in the LD fraction of F26-b using 2D-difference gel electrophoresis. The protein clustered with orthologs of thraustochytrids; however, the cluster was evolutionally different from known PAT family proteins or plant LD protein; thus, we named it thraustochytrid-specific LD protein 1 (TLDP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 54 publications
0
19
0
Order By: Relevance
“…Less direct but promising approaches were also undertaken. For example, it was shown that disrupting a thraustochytrid-specific lipid droplet protein impacts TAG accumulation in A. limacinum [138]. Because of their high number of double bonds, PUFAs are highly sensitive to reactive oxygen species, which presumably increase their rate of degradation.…”
Section: Fatty Acidsmentioning
confidence: 99%
“…Less direct but promising approaches were also undertaken. For example, it was shown that disrupting a thraustochytrid-specific lipid droplet protein impacts TAG accumulation in A. limacinum [138]. Because of their high number of double bonds, PUFAs are highly sensitive to reactive oxygen species, which presumably increase their rate of degradation.…”
Section: Fatty Acidsmentioning
confidence: 99%
“…This suggests proteins exist in suspension after the aqueous extraction procedure and cover the OBs [44]. The protein-coated fatty-acid-rich OBs were discovered in various plant and microalgal cells, and their characteristics were extensively studied due to their technological importance for the food industry [45,46]. The isoelectric point of OBs from thraustochytrids was lower than that observed in plant species (between 4 and 6) [44,47].…”
Section: Intracellular Production Of Lipids Protein Carbohydrates mentioning
confidence: 99%
“…DG, PC, and TG were analyzed by LC-ESI MS according to the method described by Ikeda et al [34]. LC-ESI MS was performed using a HPLC system (Agilent Technologies) coupled to a MS apparatus (3200 QTRAP; AB Sciex) [20]. A binary solvent gradient with a flow rate of 200 μl/min was used to separate DG, PC, and TG by reverse-phase chromatography using InerSustain C18 (2.1 x 150 mm, 5 μm; GL Sciences).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, it was reported that Aurantiochytrium and related genus have several (but not all) genes involved in elongase/desaturase pathway; however, the biological significance of these genes remains unknown [16, 17]. De novo synthesized DHA is incorporated to glycerolipids, such as triacylglycerol (TG) and phosphatidylcholine (PC), as an ester-linked acyl chain(s), and then accumulated in LDs and cell membranes [1820].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation